A WAGE SYSTEM FOR FARM WORKERS AIMED AT IMPROVING THE WELL-BEING OF THE COMMUNITY IN MANGARAN VILLAGE, MANGARAN SUBDISTRICT, SITUBONDO REGENCY - Mahfud Ali Wafa; M. Munir (IZZI: Jurnal Ekonomi Islam, 2025)
This study aims to examine the wage system for farmworkers from the perspective of fiqh muamalah, using a case study in Mangaran Village, Mangaran Subdistrict, Situbondo Regency. Using a descriptive qualitative approach, this study depicts the social and economic realities of farmworkers and analyzes them from the perspective of Islamic norms and fiqh. The findings indicate that the majority of the population in Mangaran Village earns a living as agricultural workers, particularly in the seasonal agricultural sector. The current wage system reveals disparities and injustices, particularly in terms of wages that are not commensurate with the workload borne by the workers. Although wages have increased nominally compared to the past, they do not yet fully reflect the principle of justice as mandated by Islamic fiqh, which emphasizes the importance of providing fair and timely wages. The migration of farm laborers to other sectors of employment outside the village is one consequence of the low level of welfare. This study recommends the importance of evaluating the wage system based on Islamic principles in order to achieve a balance between rights and obligations and to prevent social inequality in rural communities.